Ultrahigh-Bs, wide-temperature, high-flux and low-loss material and sintering method thereof
By controlling the sintering temperature and oxygen partial pressure, and optimizing the sintering process with auxiliary components, the problems of MnZn ferrite materials taking time and uneven grain growth during the sintering process are solved, and high Bs and low loss ferrite materials are achieved , suitable for miniaturized and high-efficiency equipment.
Patent Information
- Application Number
- CN202411379572.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing MnZn ferrite materials take a long time during the sintering process and uneven grain growth, resulting in a decrease in Bs and loss performance, which cannot meet the needs of miniaturization, lightweight, low-loss and high-efficiency equipment.
Using ultra-high Bs, wide temperature, high magnetic flux and low loss materials, the sintering process includes four stages by controlling the temperature and oxygen partial pressure: the first temperature increase stage, the second temperature increase stage, the insulation stage and the cooling stage , auxiliary components such as SiO2, V2O5, CuO are used to reduce abnormal grain growth and improve sintering density and magnetic permeability.
It realizes the high saturation flux density and low loss characteristics of the material, reduces the chance of abnormal grain growth, improves grain uniformity and hysteresis loss performance, and is suitable for miniaturization and high-efficiency equipment.
Smart Images

Figure QLYQS_1 
Figure BDA0005069562790000011 
Figure BDA0005069562790000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferrite materials, and particularly relates to an ultra-high Bs, wide temperature range, high magnetic flux, low loss material and a sintering method thereof. Background Art
[0002] At present, with the development of electronic technology, electronic products and complete machines are moving towards miniaturization and greenness, and the requirements for high magnetic permeability materials are getting higher and higher. For example, for transformers with the same inductance parameters, the higher the magnetic permeability of the magnetic material, the smaller the size of the transformer can be. It can be seen that in the field of electronic technology, the application and demand of magnetic materials with high magnetic permeability are relatively wide.
[0003] Publication number: CN 103482986 B proposes a sintering method for low-loss MnZn ferrite material, which is divided into four temperature change stages, mainly including: a, the first heating stage; b, the second heating stage; c, the heat preservation stage; d, the cooling stage. The present invention can reduce the loss of MnZn power ferrite by controlling the temperature and oxygen partial pressure during the entire sintering process of heating, heat preservation and cooling. The MnZn power ferrite prepared by the present invention has the advantages of low sintering temperature and low loss, and greatly improves the efficiency of MnZn ferrite components. However, the heating and cooling process takes a long time, the uniformity of grain growth is not enough, and in a continuous ultra-high temperature environment, the probability of abnormal grain growth caused by sintering increases, and Bs and loss performance will decrease, which cannot be applied to miniaturized, lightweight, low-loss, and high-efficiency equipment. Summary of the invention
[0004] The object of the present invention is to provide an ultra-high Bs, wide temperature, high magnetic flux, low loss material and a sintering method thereof, which has the effects of high sintering density and better Bs characteristics.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions: an ultra-high Bs, wide temperature, high magnetic flux, low loss material, including a main component and an auxiliary component, wherein the main component includes, in molar percentage:
[0006]
[0007] The total proportion of each main component is 100 mol%;
[0008] The auxiliary components include CaCO3, SnO2, Bi2O3, SiO2, TiO2, ZrO2, Ta2O5, V2O5, CuO, and C2H4O.
[0009] The present invention is further configured as follows: the main component is pre-burned to obtain a pre-burned material, and based on the total weight of the pre-burned material, the content of the auxiliary component is:
[0010]
[0011]
[0012] The present invention is further configured as follows: the auxiliary components further include 30-45 PPM of C2H4O by weight percentage.
[0013] The present invention is further configured as follows: wherein the composition and proportion of the main component are:
[0014]
[0015] The present invention is further configured as follows: relative to the total amount of the main component, the components and weight percentages of the auxiliary components are respectively:
[0016]
[0017] The present invention also provides a sintering method for the above-mentioned ultra-high Bs, wide temperature, high magnetic flux, and low loss material, comprising the following steps:
[0018] Step S1: In the first heating stage, the temperature is raised from room temperature to 300°C to 450°C at a rate of 2-10°C / min within 0.5 to 1.2 hours, and the heating stage is carried out in an air atmosphere to completely volatilize the polyvinyl alcohol in the blank;
[0019] Step S2: in the second heating stage, the temperature is raised from 300°C to 450°C to 700°C to 1350°C at a rate of 10-15°C / min within 0.8 to 1.5 hours, and the oxygen partial pressure in the sintering furnace is maintained at 20% to 25% lower than the oxygen partial pressure in air during the heating stage;
[0020] Step S3: a heat preservation stage, in which the temperature is maintained at 700° C. to 1350° C. for 2.5 to 5 hours, and the oxygen partial pressure is maintained at 0.7% to 0.9%;
[0021] Step S4: a cooling stage, in which the temperature is lowered to 100° C. at a cooling rate of 3 to 10° C. / min within 2 to 6 hours, and the equilibrium oxygen partial pressure is maintained during the cooling process;
[0022] Furthermore, the oxygen partial pressure in step S2 is maintained by evacuating the sintering furnace and then filling it with a nitrogen and oxygen mixture in an appropriate proportion to increase the furnace pressure and maintain it at a positive pressure, while the oxygen partial pressure is set to be 23% lower than the air oxygen partial pressure.
[0023] Furthermore, in step S3, the temperature is maintained at 1200° C. for 4 hours, and the oxygen partial pressure is maintained at 0.85%.
[0024] Furthermore, in step S4, the temperature is lowered to 100° C. within 5 hours and then taken out of the furnace to obtain a ferrite material.
[0025] Furthermore, the sintered ferrite material has a high saturation flux density: Bs at 25°C and 100°C are 540mT and 430mT respectively; wide temperature and low loss characteristics: Pcv<300kW / m in the range of 25°C-120°C 3 (100kHz, 200mT), Pcv<240kW / m 3 (200kHz, 125mT), Pcv<280kW / m 3 (300kHz, 100mT), Pcv<170kW / m 3 (500kHz,500mT).
[0026] The beneficial effects of the present invention are:
[0027] 1. Fe in the air 3+ To Fe 2+ The temperature is higher. In this temperature range, Fe 3+ The oxygen released during the reduction process will be enclosed in the blank to form closed pores due to the increase in the reaction contact surface of the solid phase reaction and the existence of the liquid phase. If the surrounding oxygen partial pressure is reduced, Fe 3+ The reduction temperature can be reduced to about 1000℃, so the sintering oxygen partial pressure is controlled to 1% or even lower at this temperature, which reduces the reduction reaction temperature of Fe3+ and the probability of closed pores, which is beneficial to oxygen removal and improves the sintering density.
[0028] 2. Through this densification sintering method, the oxygen exhaust temperature is reduced, the oxygen exhaust efficiency is improved, the porosity can be reduced, and the sintering temperature can be reduced at the same time, the probability of abnormal grain growth caused by high-temperature sintering can be reduced, and the grain uniformity can be improved. Therefore, the hysteresis loss can be significantly improved, the grain size is uniform, and the Bs and loss performance will be significantly optimized, which will improve energy efficiency in a wide temperature range and achieve miniaturization.
[0029] 3. The present invention adopts a low-temperature sintering method to avoid abnormal grain growth. At the same time, additives with low melting points, such as SiO2, V2O5, and CuO, are added. These additives will form a liquid phase during the sintering process, promote the solid-phase reaction, and fully exclude the pores. The density and saturation magnetic induction intensity of the material are further increased. At the same time, some high-valent ions enter the lattice. In order to meet the electrical neutrality, part of the Fe3+ is reduced to Fe2+. Since Fe2+ has a positive compensation effect on the magnetic anisotropy of ferrite, the initial magnetic permeability of the material is improved. At the same time, a stable V5-Fe2+ ion pair is formed, which reduces the jumping of electrons between Fe3+ and Fe2+, thereby increasing the resistivity of the material prepared in the present application and greatly reducing the eddy current loss.
[0030] 4. The present invention adopts a fast temperature rise sintering method. Since the densification time of the product in the temperature rise stage is short, the high temperature rise rate of the material will cause the product to quickly enter the high-temperature insulation stage. Therefore, the material components still maintain a high activity in the insulation stage, and the densification and grain growth of the material are carried out at a faster rate, the grains grow evenly, the density and saturation magnetic induction intensity of the material are increased, and ultimately the product has a higher sintering density and a higher Bs characteristic. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1: A high-frequency, wide-temperature, ultra-low-loss ferrite core, wherein the components and proportions of the main formula are:
[0033]
[0034] The total proportion of each main formula is 100 mol%.
[0035] The auxiliary components include CaCO3, SnO2, Bi2O3, SiO2, TiO2, ZrO2, Ta2O5, V2O5, CuO, and C2H4O.
[0036] The main component is pre-burned to obtain a pre-burned material. Based on the total weight of the pre-burned material, the components and weight percentages of the auxiliary components are respectively:
[0037]
[0038] Calculated by weight percentage, the auxiliary components also include 0 PPM of C2H4O4.
[0039] A sintering method for ultra-high Bs, wide temperature, high magnetic flux, and low loss materials, comprising the following steps
[0040] Step S1: In the first heating stage, the temperature is raised from room temperature to 300°C to 450°C at a rate of 2-10°C / min within 0.5 to 1.2 hours, and the heating stage is carried out in an air atmosphere to completely volatilize the polyvinyl alcohol in the blank;
[0041] Step S2: In the second heating stage, the temperature is raised from 300°C to 450°C to 700°C to 1350°C at a rate of 10-15°C / min within 0.8 to 1.5 hours, and the oxygen partial pressure in the sintering furnace is maintained at 20% to 25% lower than the oxygen partial pressure in air during the heating stage; the oxygen partial pressure in step S2 is maintained by evacuating the sintering furnace and then filling it with a nitrogen-oxygen mixed gas in an appropriate proportion to increase the furnace pressure and maintain it at a positive pressure, and the oxygen partial pressure is set to be 23% lower than the oxygen partial pressure in air
[0042] Step S3: a heat preservation stage, in which the temperature is maintained at 700° C. to 1350° C. for 2.5 to 5 hours, and the oxygen partial pressure is maintained at 0.7% to 0.9%;
[0043] In step S3, the temperature is maintained at 1200° C. for 4 hours, and the oxygen partial pressure is maintained at 0.85%.
[0044] Step S4: cooling stage, in which the temperature is cooled to 100°C at a cooling rate of 3-10°C / min within 2 to 6 hours, and the equilibrium oxygen partial pressure is maintained during the cooling process; in step S4, the temperature is reduced to 100°C within 5 hours and then taken out of the furnace to obtain the ferrite material.
[0045] Embodiment 2: A high-frequency, wide-temperature, ultra-low-loss ferrite core, wherein the components and proportions of the main formula are:
[0046]
[0047] The total proportion of each main formula is 100 mol%.
[0048] The auxiliary components include CaCO3, SnO2, Bi2O3, SiO2, TiO2, ZrO2, Ta2O5, V2O5, CuO, and C2H4O.
[0049] The main component is pre-burned to obtain a pre-burned material. Based on the total weight of the pre-burned material, the components and weight percentages of the auxiliary components are respectively:
[0050]
[0051] Calculated by weight percentage, the auxiliary components also include 10 PPM of C2H4O.
[0052] A sintering method for ultra-high Bs, wide temperature, high magnetic flux, and low loss materials, comprising the following steps
[0053] Step S1: In the first heating stage, the temperature is raised from room temperature to 300°C to 450°C at a rate of 2-10°C / min within 0.5 to 1.2 hours, and the heating stage is carried out in an air atmosphere to completely volatilize the polyvinyl alcohol in the blank;
[0054] Step S2: In the second heating stage, the temperature is raised from 300°C to 450°C to 700°C to 1350°C at a rate of 10-15°C / min within 0.8 to 1.5 hours, and the oxygen partial pressure in the sintering furnace is maintained at 20% to 25% lower than the oxygen partial pressure in air during the heating stage; the oxygen partial pressure in step S2 is maintained by evacuating the sintering furnace and then filling it with a nitrogen-oxygen mixed gas in an appropriate proportion to increase the furnace pressure and maintain it at a positive pressure, and the oxygen partial pressure is set to be 23% lower than the oxygen partial pressure in air
[0055] Step S3: a heat preservation stage, in which the temperature is maintained at 700° C. to 1350° C. for 2.5 to 5 hours, and the oxygen partial pressure is maintained at 0.7% to 0.9%;
[0056] In step S3, the temperature is maintained at 1200° C. for 4 hours, and the oxygen partial pressure is maintained at 0.85%.
[0057] Step S4: a cooling stage, in which the temperature is lowered to 100°C at a cooling rate of 3-10°C / min within 2 to 6 hours, and the equilibrium oxygen partial pressure is maintained during the cooling process; in step S4, the temperature is lowered to 100°C within 5 hours and then taken out of the furnace to obtain a ferrite material, namely HC9F7B.
[0058] The ferrite material obtained after sintering according to Example 1-2 has high saturation flux density: Bs at 25°C and 100°C are 540mT and 430mT respectively; wide temperature and low loss characteristics: Pcv<300kW / m in the range of 25°C-120°C 3 (100kHz, 200mT), Pcv<240kW / m 3(200kHz, 125mT), Pcv<280kW / m 3(300kHz, 100mT), Pcv<170kW / m 3(500kHz, 500mT). Under the same carrying power, the core volume and weight can be reduced by about 20% compared with TDK-PC95 and by about 10% compared with HC96F.
[0059] The specific comparative characteristic values are shown in Table 1 below:
[0060]
[0061] Note: ★Test condition: 200kHz, 125mT, ▲Test condition: 300kHz, 100mT, ■Test condition: 500kHz, 50mT.
Claims
1. An ultra-high Bs, wide temperature, high magnetic flux, low loss material, characterized by: It includes main components and auxiliary components, wherein the main components include, by mole percentage: Fe2O3 65~67mol% Mn3O4 28~30mol% ZnO2 3~10mol% NiO 0.5~0.7mol% The total proportion of each main component is 100 mol%; The auxiliary components include CaCO3, SnO2, Bi2O3, SiO2, TiO2, ZrO2, Ta2O5, V2O5, CuO, and C2H4O.
2. The ultra-high Bs, wide temperature, high magnetic flux, low loss material according to claim 1, characterized in that: The main component is pre-burned to obtain a pre-burned material. Based on the total weight of the pre-burned material, the content of the auxiliary component is: CaCO3 200~900PPM SnO2 150~450PPM Bi2O3 50~100PPM SiO2 50~100PPM TiO2 10~2000PPM ZrO2 20~500PPM Ta2O5 50~500PPM V2O5 50~800PPM CuO 80~600PPM.
3. The ultra-high Bs, wide temperature, high magnetic flux, low loss material according to claim 1, characterized in that: Calculated by weight percentage, the auxiliary components also include 30-45 PPM of C2H4O.
4. The ultra-high Bs, wide temperature, high magnetic flux, low loss material according to claim 1, characterized in that: The composition and ratio of the main components are: Fe2O3 65mol% Mn3O4 28mol% ZnO2 6.5mol% NiO 0.5mol%.
5. The ultra-high Bs, wide temperature, high magnetic flux, low loss material according to claim 5, characterized in that: Relative to the total amount of the main component, the components and weight percentages of the auxiliary components are: CaCO3 700PPM SnO2 350PPM 6. A sintering method for the ultra-high Bs, wide temperature, high magnetic flux, and low loss material according to any one of claims 1 to 5, characterized in that: The following steps are included: Step S1: In the first heating stage, the temperature is raised from room temperature to 300°C to 450°C at a rate of 2-10°C / min within 0.5 to 1.2 hours, and the heating stage is carried out in an air atmosphere to completely volatilize the polyvinyl alcohol in the blank; Step S2: in the second heating stage, the temperature is raised from 300°C to 450°C to 700°C to 1350°C at a rate of 10-15°C / min within 0.8 to 1.5 hours, and the oxygen partial pressure in the sintering furnace is maintained at 20% to 25% lower than the oxygen partial pressure in air during the heating stage; Step S3: a heat preservation stage, in which the temperature is maintained at 700° C. to 1350° C. for 2.5 to 5 hours, and the oxygen partial pressure is maintained at 0.7% to 0.9%; Step S4: a cooling stage, in which the temperature is lowered to 100° C. at a cooling rate of 3 to 10° C. / min within 2 to 6 hours, and the equilibrium oxygen partial pressure is maintained during the cooling process.
7. The sintering method of the ultra-high Bs, wide temperature, high magnetic flux, and low loss material according to claim 6, characterized in that: The oxygen partial pressure in step S2 is maintained by evacuating the sintering furnace and then filling it with a nitrogen and oxygen mixture in an appropriate proportion to increase the furnace pressure and maintain it at a positive pressure. At the same time, the oxygen partial pressure is set to be 23% lower than the air oxygen partial pressure.
8. The sintering method of the ultra-high Bs, wide temperature, high magnetic flux, and low loss material according to claim 6, characterized in that: In step S3, the temperature is maintained at 1200° C. for 4 hours, and the oxygen partial pressure is maintained at 0.85%.
9. The sintering method of ultra-high Bs, wide temperature, high magnetic flux, and low loss material according to claim 6, characterized in that: In step S4, the temperature is lowered to 100° C. within 5 hours and then taken out of the furnace to obtain a ferrite material.
10. The sintering method of the ultra-high Bs, wide temperature, high magnetic flux, and low loss material according to claim 9, characterized in that: The sintered ferrite material has high saturation flux density: Bs at 25℃ and 100℃ are 540mT and 430mT respectively; wide temperature and low loss characteristics: Pcv<300kW / m in the range of 25℃-120℃ 3 (100kHz, 200mT), Pcv<240kW / m 3 (200kHz, 125mT), Pcv<280kW / m 3 (300kHz, 100mT), Pcv<170kW / m 3 (500kHz, 500mT).
Citation Information
Patent Citations
High-frequency wide-temperature-range low-loss MnZn ferrite material and preparation method thereof
CN110517840A
